Tacit knowledge, embedded agency and learning: local nodes and global networks. (1st March 2014) - Lam, Alice
Abstract : Alice Lam is Professor of Organisation Studies at the School of Management, Royal Holloway University of London. Her research focuses on the relationship between organizational forms, knowledge creation and societal institutions. Her current work examines the changing nature of academic scientific work and knowledge transfer between university and industry.